A Sex Difference in Mental Rotation in Infants: Convergent Evidence. (21st August 2013) - Quinn, Paul C.; Liben, Lynn S.
<x xml:space="preserve">Abstract</x> Quinn and Liben (2008) reported a sex difference on a mental rotation task in which 3‐ to 4‐month‐olds were familiarized with a shape in different rotations and then tested with a novel rotation of the familiar shape and its mirror image. As a group, males but not females showed a significant preference for the mirror image, a pattern paralleled at the individual level (with most males but less than half the females showing the preference). Experiment 1 examined a possible explanation for this performance difference, namely, that females were more sensitive to the angular differences in the familiarized shape. Three‐ to 4‐month‐olds were given a discrimination task involving familiarization with a shape at a given rotation and preference testing with the shape in the familiarized versus a novel rotation. Females and males preferred the novel rotation, with no sex difference observed. This finding did not provide support for the suggestion that the sex difference in mental rotation is explained by differential sensitivity to angular rotation. Experiment 2 revealed that the sex difference in mental rotation is observed in 6‐ to 7‐month‐olds and 9‐ to 10‐month‐olds, suggesting that a sex difference in mental rotation is present at multiple ages during infancy.